Assessing the feasibility of distributing child poison safety messages through three existing parent information pathways. Issue 6 (3rd December 2009) - Gibbs, L; Waters, E; Robinson, J; Young, S; Hutchinson, A
Abstract : The objective of this exploratory study was to assess the feasibility of increasing parents' poison safety awareness and behaviours using existing pathways. The aim was to compare the release of true stories of child unintentional poisoning via three modes: ( a ) parent "networker"; ( b ) maternal and child health nurse; ( c ) the media. The stories spread by the parent networker were readily recalled by the parents, with examples of changed behaviour and spreading of the stories. Parents who were part of the maternal and child health nurse strategy were not able to recall the stories without prompts. The media strategy could not be implemented because of difficulties finding parents ready to publicise their story. Given that it is an exploratory study, it is not possible to draw conclusions about the effectiveness of each of the intervention strategies. However, it appears that a low-resource intervention using stories shared via parent networkers may have exciting potential as a health promotion tool. A stronger study design to examine its effectiveness is proposed.